Design and optimal control of dual-stage Stewart platform using Feedback-Linearized Quadratic Regulator. (17th October 2016) - Tourajizadeh, H.; Manteghi, S.
Abstract: Design and optimal control of a dual-stage Stewart robot is performed in this paper using sequential optimal feedback linearization method considering the dynamics of the jacks. Considering the limited length of the jacks, the possible dynamic workspace of this robot is extremely limited. Dual-stage platform version of this robot is designed and proposed in this paper to improve this limitation. As a result, the dynamic workspace of the robot is increased by increasing the degrees of freedom (DOFs) of the system. Modeling and dynamics of the new proposed system are developed considering the dynamics of the jacks. Besides, the robot is controlled with the highest accuracy and the lowest energy using an optimal control strategy based on Feedback-Linearized Quadratic Regulator (FLQR). Two sequential controlling loops are employed for simultaneous control of the joint space and work space of the robot. The efficiency of the proposed manipulator toward increasing the workspace of the robot and also the accuracy of the proposed controller are investigated using MATLAB for a dual-stage Stewart robot. The kinematics and kinetics of the robot are extracted, the proposed controller is implemented and the results are analyzed which show the efficiency of the proposed structure and controlling method. Graphical Abstract: